The Personalization of Electoral Rules: How Shifting Influence From Selectors to Voters Affects Party Unity. (March 2022) - Däubler, Thomas
How does making electoral systems more candidate-centered affect party unity? Using a principal-agent perspective, this study makes three contributions to the literature on this topic. Conceptually, it suggests thinking about the incentives due to personalization as arising from a shift in electoral impact from party selectors to voters. Theoretically, it incorporates this notion into a spatial model of parliamentary voting that also considers principals' monitoring capacities. From the resulting framework follows a rich set of observable implications, notably that candidate-centered electoral systems facilitate rather than undermine collective action within parliamentary parties under certain conditions. Empirically, this study then analyzes the 2010 reform of Sweden's flexible-list proportional representation system, which changed the preference vote threshold. As expected, I find that when extreme (district-based) selectors disagree with the moderate bills supported by the party group leadership, personalized rules incentivize politicians to support these policies and vote in unison.